Short term hearing results in patients with otosclerosis after stapedotomy in a tertiary care center. - Rayamajhi , P; Rauniyar , N (Journal of Institute of Medicine Nepal, 2018)
Introduction: Stapedotomy done for otosclerosis is one of the finest middle ear surgery and needs great expertise. The present study is done to evaluate the short-term hearing results in patients with otosclerosis and treated with primary stapedotomy.Methods: A retrospective chart review of patients after stapedotomy surgery was done from April 2011 to October 2016. Stapedotomy was performed under local anesthesia using a Teflon piston under local anesthesia. The patients were followed up after 6 weeks for the assessment of the hearing status. The hearing assessment was done using the Air Bone gap improvement and Air Bone gap closure (AB gap closure) pre and postoperatively.Results: Total of 73 cases were retrieved from hospital database. 3 cases were excluded and analysis of only 70 cases was done. Among the total patients 85.71% of the patients had bilateral involvement of the disease. The overall mean pre-operative pure tone Air conduction average was 55.66 dB, SD 11.576 (95% CI; 52.57-59212), while the overall mean post -operative pure tone average was 17.63 dB, SD 11.958 (95% CI; 14.70-21.57). This difference was found to be statistically significant (p = 0.000). The overall mean pre-operative air bone gap was 37.65 dB and the overall mean post -operative air bone gap was 18.47dB. This difference was found to be statistically significant (p = 0.000).Conclusion: This study confirms that stapedotomy for clinical otosclerosis is a safe and successful treatment for short-term hearing improvement. Both the AC threshold and AB gap closure showed significant improvement postoperatively.